Impact of external debt on exchange rate in Nigeria - Saheed, Titilayo; E. Victor, Oriavwote (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2025)
Purpose: This study investigates the impact of external debt on exchange rate movements in Nigeria from 1981 to 2023, assessing how external debt, debt servicing, and foreign reserves jointly influence exchange rate stability within the framework of the Keynesian Theory of Public Debt. Methodology: An ex-post facto research design and time series analytical approach were adopted, using secondary data sourced from the CBN Statistical Bulletin and the World Bank database. The Autoregressive Distributed Lag (ARDL) technique was applied to estimate both the short-run and long-run dynamics among the variables. The bounds test confirms a significant long-run relationship among the variables (F-statistic = 8.887 > 4.66 at 1% level). Results and conclusion: In the long run, external debt (LEXDT) and foreign reserves (LFORS) exert positive and statistically significant effects on the exchange rate, while debt servicing (LDBSV) exerts a negative but statistically insignificant effect. The error correction term (ECM = –0.2007) is negative and significant, indicating that about 20% of short-run deviations are corrected annually. With an R-squared of 0.994, the model explains over 99% of exchange rate variations. The study concludes that external debt and foreign reserves are major determinants of Nigeria’s exchange rate dynamics, whereas rising debt servicing worsens currency performance. Implication of findings: The findings imply that Nigeria must adopt a cautious but productive borrowing strategy, channel external loans into foreign-exchange-generating investments, strengthen debt management practices, build a robust foreign reserve base, and implement a balanced fiscal–monetary policy mix to enhance exchange rate stability and support sustainable macroeconomic growth.